WATER CONSERVATION PRACTICES: LEARNINGS FROM VERNACULAR WISDOM AND THEIR CONTEMPORARY APPLICABILITY - Ar. Gaurav Singh, Prof (Dr) Manoj Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Water is an essential resource for human survival, but the sources of water like rivers, underground reserves, glaciers etc., are getting polluted, depleting and becoming scarce over the years with the increase of population, uncontrolled extraction and climate change. This is the situation not of one city or a state but this is happening globally. With the ever changing climate conditions and rapid urbanization, the most scarce resource is potable water. This paper makes a case that the heritage and vernacular practices, that have been tested by generations, can help us in the conservation of water and how they can be applied in our contemporary practices for human survival.